Character Discrimination Analysis in the Novel Maryam by Okky Madasari - Somadi Sosrohadi; Diana Wulandari (Hasanuddin University, 2022)
This study analyzes the types of discrimination that occur in the main character Maryam who was born as an Ahmadiyah adherent in the novel Okky Madasari. The formulation of the problem from this research is, what are the elements that cause discrimination against the character Maryam and what are the types of discrimination. The method that the researcher considers qualified to assist this research is the descriptive-qualitative method. This type of discrimination analysis uses Fulthoni's theory, which explains the types of discrimination from ethnicity, race, and religion/belief to gender and gender issues (social roles due to gender), and reveals the elements of discrimination that the author uses. new structural theory. Talking about the scope of social life, we will be carried away in various complex behaviors in society, which are formed in the dimensions of life and can be observed and traced to capture human existence. In Okky Madasari's novel Maryam, the main character Maryam experiences various life conflicts in the form of discrimination. The emergence of this discrimination is the result of the birth of Maryam's character as Ahmadiyah which is seen as a deviant sect by the community.